Photoperiod and temperature as dominant environmental drivers triggering secondary growth resumption in Northern Hemisphere conifers - Huang, Jian-Guo; Ma, Qianqian; Rossi, Sergio; Biondi, Franco; Deslauriers, Annie; Fonti, Patrick; Liang, Eryuan; Mäkinen, Harri; Oberhuber, Walter; Rathgeber, Cyrille B K; Tognetti, Roberto; Treml, Václav; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Wood formation consumes around 15% of the anthropogenic CO2 emissions per year and plays a critical role in long-term sequestration of carbon on Earth. However, the exogenous factors driving wood formation onset and the underlying cellular mechanisms are still poorly understood and quantified, and this hampers an effective assessment of terrestrial forest productivity and carbon budget under global warming. Here, we used an extensive collection of unique datasets of weekly xylem tissue formation (wood formation) from 21 coniferous species across the Northern Hemisphere (latitudes 23 to 67°N) to present a quantitative demonstration that the onset of wood formation in Northern Hemisphere conifers is primarily driven by photoperiod and mean annual temperature (MAT), and only secondarily by spring forcing, winter chilling, and moisture availability. Photoperiod interacts with MAT and plays the dominant role in regulating the onset of secondary meristem growth, contrary to its as-yet-unquantified role in affecting the springtime phenology of primary meristems. The unique relationships between exogenous factors and wood formation could help to predict how forest ecosystems respond and adapt to climate warming and could provide a better understanding of the feedback occurring between vegetation and climate that is mediated by phenology. Our study quantifies the role of major environmental drivers for incorporation into state-of-the-art Earth system models (ESMs), thereby providing an improved assessment of long-term and high-resolution observations of biogeochemical cycles across terrestrial biomes.
Keywords: photoperiod; Seasons; temperature; Climate Change; Photoperiod; ekosystém; stromy; cévnaté rostliny; teplota; fotoperioda; Wood; globální oteplování; Tracheophyta; wood formation; Xylem; Trees; klimatické změny; Climate; Models, Biological; Global Warming; xylém; Temperature; lesy; dřevo; biologické modely; podnebí; Ecosystem; roční období; Northern Hemisphere conifer; xylogenesis; Forests